The Effect of Providing Exclusive Breastfeeding and Complementary food for breastfeeding on The Incident Of Stunting in Toddler in The Kalisari Area Pasar Rebo District - Susanti, Devi; Fahri, Ahmad; Wiratikusuma, Yohana (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2024)
Children are sometimes faced with problems of satisfaction with Exclusive Breastfeeding and MP Breastfeeding, which involves problems of development and progress. One of the health problems experienced by children is obstacles. The obstacles are a condition of failure to grow and develop in children under five (babies under five years) which is caused by a continuous lack of healthy food intake so that the child is too short for his age.Malnutrition happens when the baby is within the womb and within the early days after the child is born, be that as it may, hindering as it were shows up after the infant is 2 a long time ancient by measuring body length and stature. This research uses correlation analytics with a cross sectional approach, namely a type of research that emphasizes measuring/observing the independent variable and dependent variable data only once. The population in this study were all toddlers in Kalisari District. Pasar Rebo, Samples taken from toddlers in Kalisari District. Rebo Market as many as 30 toddlers. Sampling techniques are divided into two large groups, namely random techniques (probability sampling) and non-random techniques (nonprobability sampling). In this research, random sampling is used, which is the simplest type of probability. The research results are processed through (Editing, Coding, Scoring, Tabulating, Interpreting). The results are presented in the form of tables and narratives. The results showed that all toddlers with a history of good MP-ASI had a height in the normal category of 20 people (66.7%). All toddlers with adequate MP-ASI are in the short category as many as 7 people (23.3%). All toddlers with a history of insufficient MP-ASI were in the very short category, as many as 3 people (10%). Conclusion There is an influence between the history of exclusive breastfeeding and MP-ASI on the incidence of stunting in toddlers in Kalisari Village, Pasar Rebo District